DECARBONISING THE PALM OIL VALUE CHAIN: A REVIEW OF SUSTAINABILITY CERTIFICATIONS, POLICY ALIGNMENT, AND TECHNOLOGICAL READINESS FOR NET-ZERO TARGETS - Judijanto, Loso (Seven Editora, 2025)
The global greenhouse gas footprint of the palm oil sector is substantial, making the decarbonisation of its entire value chain an urgent priority. This study aims to critically review the effectiveness of sustainability certifications, policy frameworks, and technological innovations in supporting net-zero targets within the palm oil sector. Employing a qualitative literature review approach, the research synthesises findings from peer-reviewed journals, policy reports, and institutional publications dated between 2015 and 2025. Data collection was conducted through systematic searches in databases such as Scopus, Web of Science, and ScienceDirect, selecting 80 relevant studies based on strict inclusion criteria related to emissions data, policy analysis, and technological readiness. Thematic analysis was applied to interpret and integrate the collected literature. Results indicate that sustainability certifications like RSPO, ISPO, and MSPO contribute to measurable emissions reductions, yet face challenges related to enforcement and regional disparities. Policy alignment is fragmented, with national targets often undermined by inconsistent implementation and overlapping regulatory mandates. Technological readiness varies significantly, with large-scale producers adopting methane capture and precision agriculture technologies, while smallholders experience limited access due to financial and technical constraints. The study concludes that coordinated integration of certification schemes, robust policy frameworks, and equitable technology dissemination is essential to accelerate decarbonisation in the palm oil value chain. Future research should explore scalable support mechanisms for smallholders and investigate innovative policy models to enhance sector-wide climate action. DOI: https://doi.org/10.56238/sevened2025.021-084